Afferent loop obstruction induced by gallstone ileus after Whipple procedure: a case report and literature review - Shen, Danfeng; Xu, Haibin; Chang, Peng; Gu, Qiang; Xu, Hongxing (Frontiers in Medicine, 2025)
Afferent loop obstruction (ALO) induced by gallstone ileus after pancreaticoduodenectomy (PD) is rare. We present a case of ALO after the Whipple procedure in a 62-year-old male with a rare cause of gallstone ileus. He was admitted to the hospital with epigastric pain, fever, and jaundice two years after experiencing intermittent abdominal pain. With the help of computed tomography (CT) and magnetic resonance cholangiopancreatography (MRCP) gallstone ileus was confirmed and the patient underwent emergency surgery. Intraoperative findings indicated that internal herniation, adhesions and a stuck intra-pancreatic duct catheter caused gallstone formation and eventually led to ALO. The patient underwent prompt surgical intervention and ultimately recovered well. This case report holds a significant potential to contribute to the focus on the details of the Whipple procedure to prevent ALO and gallstone ileus.